THE IMPLEMENTATION OF STUDENTS' RELIGIOUS DEVELOPMENT IN HIGH SCHOOL LEVEL - Fikri Audah NSY (STAI Tuanku Tambusai, 2021)
In several cases of violations committed by students, many parties have questioned the extent to which religious education lessons have succeeded in changing children's behavior. The behavior (akhlaq) of Muslim students is ideally always based on Islamic values, religiosity. There are many ways to increase students' self-religion at the high school level—both through intracurricular and extracurricular approaches, spiritual-physical. In short, the school as an education provider tries to create a supportive climate with all the power and effort to better student religious attitudes than before. For example, SMA 3 Muhammadiyah Surakarta, SMK Ibnu Taimiyah Pekanbaru, and SMA Daarut Tauhid Bandung have implemented various programs to increase student religiosity. Including from the spiritual side; 1) religious lectures 'kultum', 2) alms, 3) obligatory and sunnah prayers at school, 4) group reading the Al-Qur'an. And also from the physical side; 1) archery, 2) horse riding, 3) martial arts. The activities mentioned above are proven to impact the development of students' religious attitudes positively.